Key territories of the Ingulsky regional ecological corridor: characteristics, interconnection and optimization (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The scheme of key territories of the Ingulsky ecological corridor is proposed (1 of regional, 15 of local level). Characteristics of plant cover is given. Interconnections between these territories and adjacent territories are analyzed. The assessment of their efficiency, based on coherence, accessibility, centrality and fragmentation rates is conducted. The necessity of establishhing two additional local ecological corridors is proved for optimization of the efficiency of ecological network existed (Pravoberezhno-Ingulsky and Livoberezhno- Ingulsky).
Keywords: Ingulsky ecological corridor, key territories, efficiency assessment, optimization.